Financial Performance and Company Values: A Study in the Banking Sector - Proud, Laura Michelia; Suhendra, Euphrasia Susy (Indatu Journal of Management and Accounting, 2023)
A company aims to boost its overall value by maximizing stock prices. The significance of banking in an economy, especially for fund intermediation and credit, makes banking companies on the Indonesia Stock Exchange valuable subjects for research. This research aims to examine the factors influencing the value of companies in the banking sector listed on the Indonesia Stock Exchange from 2016 to 2022. The study employs a quantitative method, collecting data from the annual financial reports of banks listed on the Indonesia Stock Exchange. The research results indicate that Profitability, Liquidity, and Company Growth significantly influence Company Value, while Capital Structure does not significantly affect Company Value. Thus, it implies that financial performances give partial impact to the researched company values. Unlike the other from the financial performances being discussed, the capital structure does not give significant impact towards the company value.